Treasury Balances Dangerous in France (Quarterly Journal of Economics, 1887)
Treasury Balances Dangerous in France Get access The Quarterly Journal of Economics, Volume 1, Issue 4, July 1887, Page 469, https://doi.org/10.1093/qje/1.4.469 Published: 01 July 1887